Integrative Role of Hyperbaric Oxygen Therapy on Healthspan, Age-Related Vascular Cognitive Impairment, and Dementia - Balasubramanian, Priya; Delfavero, Jordan; Nyul-Toth, Adam; Tarantini, Amber; Gulej, Rafal; Tarantini, Stefano (Frontiers in Aging, 2021)
Growing life expectancy will contribute to the on-going shift towards a world population increasingly comprised of elderly individuals. This demographic shift is associated with a rising prevalence of age-related diseases, among all age-related pathologies it has become crucial to understand the age-associated cognitive changes that remain a major risk factor for the development of vascular cognitive impairment and dementia (VCID). Furthermore, age-related Alzheimer’s disease and other neurogenerative diseases with vascular etiology are the most prominent contributing factors for the loss of cognitive function observed in aging. Hyperbaric Oxygen Therapy (HBOT) achieves physiologic effects by increasing oxygen tension (PO2), raising oxygen tissue levels, decreasing intracranial pressure and relieving cerebral edema. Many of the beneficial effects of HBOT exert their protective effects at the level of the microcirculation. Furthermore, the microcirculation’s exquisite pervasive presence across every tissue in the body, renders it uniquely able to influence the local environment of most tissues and organs, including the brain. As such, treatments aimed at restoring aging-induced functional and structural alterations of the cerebral microcirculation may potentially contribute to the amelioration of a range of age-related pathologies including vascular cognitive impairment, Alzheimer’s disease, and vascular dementias. Despite the presented evidence, the efficacy and safety of HBOT for the treatment of age-related vascular cognitive impairment and dementia remains understudied. The present review aims to examine the existing evidence indicative of a potential therapeutic role for HBOT-induced hyperoxia against age-related cerebromicrovascular pathologies contributing to cognitive impairment, dementia and decreased healthspan in the elderly..